Land rights knowledge and conservation in rural Ethiopia: Mind the gender gap - Quisumbing, Agnes R.; Kumar, Neha (International Food Policy Research Institute, 2014)
Using the 2009 round of the Ethiopian Rural Household Survey, this paper examines the medium-term impact of the land registration on investment behavior by households, particularly the adoption of soil conservation techniques and tree planting. It investigates whether men’s and women’s knowledge of their property rights under the land registration (as measured by answers to a list of questions regarding the provisions of the registration, covering such areas as tenure security, land transfer rights, and rights related to gender equity and inheritance) has an impact on these investments.